2016
DOI: 10.1007/s00421-016-3416-9
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in the standing position reflects training adaptation in professional soccer players

Abstract: HRV in the standing position could monitor training adaptation in intermittent sports contrary to the indicator usually employed in endurance sports. However, the significance of the HRV change in the standing position during training remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
3
25
0
1
Order By: Relevance
“…Standing sympathetic activation was demonstrated with increases in HR, LF,LFnu,and LF/HF (20,43,31,and 80%,respectively). Our results are in accordance with previous studies showing that standing HRV better reflects training loads of soccer players while usual supine HRV indices remain unchanged (Ravé and Fortrat, 2016).…”
Section: Figuresupporting
confidence: 93%
See 3 more Smart Citations
“…Standing sympathetic activation was demonstrated with increases in HR, LF,LFnu,and LF/HF (20,43,31,and 80%,respectively). Our results are in accordance with previous studies showing that standing HRV better reflects training loads of soccer players while usual supine HRV indices remain unchanged (Ravé and Fortrat, 2016).…”
Section: Figuresupporting
confidence: 93%
“…Among these parasympathetic indices, the Roots Mean Square of the Successive Differences (RMSSD) has been widely used given its robustness for aerobic training monitoring (Buchheit, 2014). However, previous studies in team sports showed contradictory results with regard to RMSSD (Flatt et al, 2016(Flatt et al, , 2017Nakamura et al, 2015;Ravé and Fortrat, 2016). For instance, its logarithmic version (Ln RMSSD) after submaximal efforts seems useless for identifying players' adaptation to training loads (Thorpe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zipf’s law represents another argument for cardiovascular self-organized criticality but without physiological and medical implications, contrary to Gutenberg Richter’s law [ 2 , 4 , 10 ]. Beat-by-beat recordings of the heart rate are easy to obtain by means of commercially available heart rate monitors, facilitating the study of its complex dynamics [ 13 , 14 ]. However, it is still unknown whether Gutenberg Richter’s law, determined by blood pressure and heart rate recordings, and Zipf’s law, determined only by heart rate recordings, provide the same information.…”
Section: Introductionmentioning
confidence: 99%